Effect of porosity on the bending analysis of various functionally graded sandwich plates. (15th March 2019) - Daikh, Ahmed Amine; Zenkour, Ashraf M
Abstract: A new porosities distribution is proposed for bending analysis of new model of functionally graded material (FGM) sandwich plates. Material properties of FGM layers are assumed to vary continuously across the plate thickness according to either power-law or sigmoid function in terms of the volume fractions of the constituents. The face layers are considered to be FG across each face thickness while the core is made of a ceramic homogeneous layer. New higher-order deformation theory is proposed to derive the field equations of the FG sandwich plates with simply-supported edge conditions. Numerical results are presented to show the effect of the material distribution, the sandwich plate geometry and the porosity on the deflections and stresses of FG sandwich plates. The accuracy of this theory is ascertained by comparing it with other published results.